2023
DOI: 10.3390/jof9020133
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma-Mediated ZnO Nanoparticles and Their Antibiofilm and Antibacterial Activities

Abstract: Antimicrobial resistance is a major global health concern and one of the gravest challenges to humanity today. Antibiotic resistance has been acquired by certain bacterial strains. As a result, new antibacterial drugs are urgently required to combat resistant microorganisms. Species of Trichoderma are known to produce a wide range of enzymes and secondary metabolites that can be exploited for the synthesis of nanoparticles. In the present study, Trichoderma asperellum was isolated from rhizosphere soil and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
(69 reference statements)
2
3
0
Order By: Relevance
“…These results were in relation with data reported in Salvia officinalis ZnONPs for zinc, oxygen, and organic components [52] . TEM analysis of Citrullus colocynthis ZnONPs showed diameters ranging from 15 to 96 nm and had shapes like rods and hexagons [53] and [54] Observed well‐defined crystal planes in high‐resolution TEM images of ZnO particles in a study. A recent analysis, as confirmed by [55] on ZnO NPs synthesized by Eriobotrya japonica Lea.…”
Section: Discussionsupporting
confidence: 88%
“…These results were in relation with data reported in Salvia officinalis ZnONPs for zinc, oxygen, and organic components [52] . TEM analysis of Citrullus colocynthis ZnONPs showed diameters ranging from 15 to 96 nm and had shapes like rods and hexagons [53] and [54] Observed well‐defined crystal planes in high‐resolution TEM images of ZnO particles in a study. A recent analysis, as confirmed by [55] on ZnO NPs synthesized by Eriobotrya japonica Lea.…”
Section: Discussionsupporting
confidence: 88%
“…Fringes were observed in the TEM selected area electron diffraction (SAED) pattern at distances of 3.0125, 2.7129, and 2.4157, respectively, corresponding to the (100), (002), and (101) hkl planes ( Baruah et al, 2021 ) ( Figures 3C,D ), indicating the crystalline nature of the NPs. This is strongly corroborated by the XRD results, which demonstrates that the particles were crystalline ( Rambabu et al, 2021 ; Shobha et al, 2023 ).…”
Section: Resultssupporting
confidence: 73%
“…Shobha et al also reported the antibiofilm potential of ZnO NPs synthesized from Trichoderma asperellum isolated from rhizosphere soil. They demonstrated a significant increase in antiadherence and antibiofilm activity of nanoparticles by increasing their concentration [ 143 ].…”
Section: Antibiofilm and Anti Quorum Sensing Activities Of Mycogenic ...mentioning
confidence: 99%